Dread and Risk Elimination Premium for the Value of a Statistical Life - Sara Olofsson; Ulf-G. Gerdtham; Lars Hultkrantz; Ulf Persson (Lund University, School of Economics and Management, Department of Economics, 2016)
The Value of a Statistical Life (VSL) is a widely used measure of the value of mortality risk reduction. Since VSL should reflect preferences and attitudes to risk, there are reasons to believe that it varies depending on the type of risk involved. It has been argued that cancer should be considered a "dread disease", which supports the use of a "cancer premium". The objective of this study is to elicit the existence and size of a cancer premium (for pancreatic cancer and multiple myeloma) in relation to road traffic accidents, sudden cardiac arrest and Amyotrophic Lateral Sclerosis (ALS). Data was collected from 500 individuals in the Swedish general population 50 -74 years old using a web-based questionnaire. Preferences were elicited using the Contingent Valuation method, and a split-sample design was applied to test for scale sensitivity. VSL differs significantly between contexts, being highest for ALS and lowest for road traffic accident. A premium (26-76 %) for cancer was found in relation to road traffic accidents, but not in relation to ALS and sudden cardiac arrest. The premium was higher for cancer with a shorter time from diagnosis to death. Eliminating risk was associated with a premium of around 17 %. Evidence of scale sensitivity was found when comparing WTP for all risks simultaneously. This study shows that there exist a dread premium and risk elimination premium. These factors should be considered when searching for an appropriate value for economic evaluation and health technology assessment.
Keywords: D61; D80; I18; J17; 330; willingness to pay; value of a statistical life; cancer; contingent valuation; risk elimination